Molecular characterization of swine acute diarrhea syndrome coronavirus detected in Vietnamese pigs - Nam Phuong Le; Bac Tran Le; Van Phan Le; Jung-Eun Park (Veterinary Research)
Abstract Swine acute diarrhea syndrome coronavirus (SADS-CoV) is a novel porcine coronavirus that was recently identified in southern China in 2017. At present, there is a lack of nationwide epidemiological investigations of the newly emerged SADS-CoV. Because Vietnam is geographically adjacent to southern China, many diseases have spread from China to Vietnam. To assess SADS-CoV transmission to Vietnam, we conducted a retrospective study to detect SADS-CoV in samples collected from pig farms in northern Vietnam. Among the 69 fecal samples tested, 5 were positive for SADS-CoV. The spike gene sequence showed high genetic homology with strains circulating in China. Our study is the first to show that SADS-CoV has spread from China to Vietnam and highlights the need for global epidemiological investigations of SADS-CoV.